Let f : [ 0 , 1 ] → R be a continuous , differentiable function. Define
A = max ∣ f ( x ) ∣ or B = ∫ 0 1 ∣ f ′ ( x ) ∣ + ∣ f ( x ) ∣ d x
Which of the following inequalities is always correct?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that, the integral ∫ 0 1 ∣ f ′ ( x ) ∣ d x is equal to the total variation of the differentiable function f . Hence, by definition ∫ 0 1 ∣ f ′ ( x ) ∣ d x ≥ 0 ≤ x ≤ 1 max ∣ f ( x ) ∣ − 0 ≤ x ≤ 1 min ∣ f ( x ) ∣ .
Suppose that m = in f x ∈ [ 0 , 1 ] f ( x ) and M = sup x ∈ [ 0 , 1 ] f ( x ) . Find c , d ∈ [ 0 , 1 ] such that f ( c ) = m and f ( d ) = M .
Suppose first that f is non-negative throughout [ 0 , 1 ] . Then 0 ≤ m ≤ M and A = M . Since f ( x ) ≥ m for all x ∈ [ 0 , 1 ] , it follows that m = ∫ 0 1 m d x ≤ ∫ 0 1 f ( x ) d x = ∫ 0 1 ∣ f ( x ) ∣ d x Also M − m = ∣ ∣ ∣ ∣ ∣ ∫ c d f ′ ( x ) d x ∣ ∣ ∣ ∣ ∣ ≤ ∣ ∣ ∣ ∣ ∣ ∫ c d ∣ f ′ ( x ) ∣ d x ∣ ∣ ∣ ∣ ∣ ≤ ∫ 0 1 ∣ f ′ ( x ) ∣ d x Adding these results tells us that M ≤ B , and so A ≤ B in this case. A similar argument shows that A ≤ B when f is non-positive throughout [ 0 , 1 ] .
Suppose now that f can be both positive and negative. Thus m < 0 < M and A = m a x ( ∣ m ∣ , M ) . Find u ∈ [ 0 , 1 ] such that f ( u ) = 0 . Then ∣ m ∣ = ∣ ∣ ∣ ∣ ∫ u c f ′ ( x ) d x ∣ ∣ ∣ ∣ ≤ ∫ 0 1 ∣ f ′ ( x ) ∣ d x ≤ B M = ∣ ∣ ∣ ∣ ∣ ∫ u d f ′ ( x ) d x ∣ ∣ ∣ ∣ ∣ ≤ ∫ 0 1 ∣ f ′ ( x ) ∣ d x ≤ B and hence A = m a x ( ∣ m ∣ , ∣ M ∣ ) ≤ B in this case as well.
Very interesting approach.
This question is actually a corollary of fundamental theorem of calculus , namely that
f ( b ) − f ( a ) = ∫ a b f ′ ( x ) d x ≤ ∫ a b ∣ f ′ ( x ) ∣ d x
We then choose suitable values, namely letting b be the x value that maximizes f ( x ) and a be the x value that minimizes f ( x ) as you did above. I like this as an intriguing exercise after learning the fundamental theorem.
Problem Loading...
Note Loading...
Set Loading...
Recall that the fundamental theorem of calculus states
f ( b ) − f ( a ) = ∫ a b f ′ ( x ) d x
Thus, for all a , b ∈ [ 0 , 1 ] , we have
∣ f ( b ) ∣ − ∣ f ( a ) ∣ ≤ ∣ f ( b ) − f ( a ) ∣ = ∣ ∣ ∣ ∣ ∣ ∫ a b f ′ ( x ) d x ∣ ∣ ∣ ∣ ∣ ≤ ∫ a b ∣ f ′ ( x ) ∣ d x ≤ ∫ 0 1 ∣ f ′ ( x ) ∣ d x
Now, let b be the x-value that maximizes ∣ f ( x ) ∣ , and a be the x-value that minimizes ∣ f ( x ) ∣ . Then, we have
∣ f ( a ) ∣ = min ∣ f ( x ) ∣ ≤ ∫ 0 1 ∣ f ( x ) ∣ d x
Thus
max ∣ f ( x ) ∣ = ∣ f ( b ) ∣ ≤ ∣ f ( a ) ∣ + ∫ 0 1 ∣ f ′ ( x ) ∣ d x = ∫ 0 1 ∣ f ′ ( x ) ∣ + ∣ f ( x ) ∣ d x
We have inequality whenever any of the inequalities do not hold. E.g. if f ( x ) has both positive and negative values, or if f ′ ( x ) has both positive and negative values, of when { a , b } = { 0 , 1 } along with non-zero f ′ ( x ) , f ( x ) outside of [ a , b ] .